2023
DOI: 10.1108/jmp-01-2023-0030
|View full text |Cite
|
Sign up to set email alerts
|

How's the boss? Integration of the health-oriented leadership concept into the job demands-resources theory

Abstract: PurposeHealth-oriented leadership (HoL) encompasses leaders' health behaviors and attitudes toward their followers (StaffCare) and themselves (SelfCare), and there is ample evidence of its positive effects on employee well-being. However, research on the antecedents of StaffCare is still in its infancy and does not account for within-person variability. Therefore, the authors adopt a leader-centered perspective and propose a serial mediation model that links leaders' intrapersonal fluctuations in job resources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
(127 reference statements)
0
6
0
Order By: Relevance
“…Further, similarly to our findings, an interview study with leaders from a healthcare organization in Canada found that corporate culture was a relevant enabler of remote work, which included supporting staff, positive perceptions of remote work, a value-focused organization, and embracing geographically dispersed teams [ 53 ]. However, independent of remote work context, studies on HoL investigated leaders’ job resources [ 32 ] and demands [ 48 ], organizational health climate [ 35 , 36 ]), high-performance work practices or health-oriented human resources management strategies [ 37 ] as antecedents of HoL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, similarly to our findings, an interview study with leaders from a healthcare organization in Canada found that corporate culture was a relevant enabler of remote work, which included supporting staff, positive perceptions of remote work, a value-focused organization, and embracing geographically dispersed teams [ 53 ]. However, independent of remote work context, studies on HoL investigated leaders’ job resources [ 32 ] and demands [ 48 ], organizational health climate [ 35 , 36 ]), high-performance work practices or health-oriented human resources management strategies [ 37 ] as antecedents of HoL.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, there are generally few studies on conducive conditions for HoL [ 11 ]. For the traditional, face-to-face work context, leaders’ own SelfCare [ 32 ], but also job resources related to social relationships (such as social support by colleagues [ 33 ], team health climate [ 34 ] or organizational health climate [ 35 , 36 ]) as well as to work organization (such as high-performance work practices or health-oriented human resources management strategies [ 37 ]) were found to positively influence HoL. For the digital, remote work context, only one pre-pandemic qualitative explorative study assessed work characteristics influencing the application of HoL in virtual teams [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…SelfCare is part of the Health-oriented Leadership concept (Franke et al, 2014) which differentiates between StaffCare (promoting followers' health) and SelfCare (promoting one's own health). SelfCare is well-studied for traditional work contexts (Grimm et al, 2021;Kaluza et al, 2021;Klug et al, 2022;Arnold and Rigotti, 2023), but it is an open question how important SelfCare is in digital and hybrid work arrangements, i.e., when SelfCare is displayed at home.…”
Section: Selfcare In the Remote Work Contextmentioning
confidence: 99%
“…So far, SelfCare has been mainly studied in the traditional work context. Ample research has already shown that SelfCare at the workplace (on-site) is beneficial to employees' health (Grimm et al, 2021;Kaluza and Junker, 2022;Arnold and Rigotti, 2023). But it is unknown, if SelfCare is also important when working at home.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation